The application of FRAX values to determine the distribution of risk factors for Osteoporosis in Postmenopausal women - Tri Hari Irfani (Public Health of Indonesia)
Background: Osteoporosis is the most common bone disease in humans that causes a bone fracture occurring without trauma or after a minimum trauma as complication.